Introduction - Kartawinata, K.; Sheil, Douglas; Wollenberg, Eva Karoline; Levang, P.; Machfudh (CIFOR and ITTO, 2002)
It is an introduction of CIFOR's research in Bulungan, Kalimantan with the Ministry of Forestry in Indonesia and ITTO. CIFOR's strategic research is focused on policy issues to enable more informed, productive, sustainable and equitable decisions about the management and use of forests. CIFOR works closely with ITTO and FORDA (the Forestry Research and Development Agency, Ministry of Forestry, Indonesia) as important strategic partners in the Bulungan model forest project phase 1, 1997-2001. The aim of the research is to carry out a systematic investigation of how to achieve forest sustainability for a 'large forest landscape' in the humid tropics, where diverse, rapidly changing and often conflicting land use demand exist. The specific objectives of the activities conducted with ITTO support are: 1) Assessment of the effect of reduced-impact logging (RIL) on biodiversity, conservation, ecology and socio-economics, 2) Assessment of rural development trends and future policy options including the effects of macro-level development activities on people dependent on the forest.